Estudio diacrónico y sincrónico del objeto indirecto en el español peninsular y de América (Vol. 57) - Silvia Becerra Bascuñán (Etudes Romanes, 2007)
This work is a contribution to the understanding of some diachronic and synchronic aspects of the grammatical relation Indirect Object hitherto not studied: (i) grammaticalization (from the 12th to the 21st century) of cross reference -double representation- of indirect object in the light of the theory of 'drift' of Henning Andersen; (ii) revision of the conceptualization of grammatical relations within functional linguistics, on one hand of Simon Dik, on the other of Michael Herslund. The study is based on a corpus of texts (2 mill. running words) of Peninsular and American Spanish, dating from the end of the 19th to the beginnings of the 21st century. All kinds of genres - written as well as spoken - have been studied.